Assessment of the status of improved F&E trachoma control practices among children of agro-pastoralists in Southern Ethiopia: a mixed design survey using theory of triadic influences - Serawit Lakew; Genet Asefa; Zerihun Zerdo (BMC, 2023)
Abstract Background Ethiopia is one of the countries with heavy trachoma burdens states globally. More than 75 million people in Ethiopia live in the trachoma endemic zones. Most populations with neglected tropical diseases (NTDs) live in hard-to-reach residences because of landscape and socio-cultural variances. This survey assessed the status of improved Face hygiene and Environmental cleanliness (F&E) trachoma control practices in children 1-9 years of age. Methods A mixed-method study design was applied concurrently. Enumeration was done through interviews using the standard tool and observational technique. Focus Group discussions (FGDs) and Key informant Interviews (KIIs) were used to conduct the qualitative arm. Confounders were controlled by modeling with multivariable logistic regression. Results For the Quantitative survey: The response rate was 99.8% of participants. The proportion with improved practice was 8%. About 13.9% of a child washed their faces and were visibly clean. About 15.2% of the households had an observable clean environment. High Wealth index, Perceived ability, knowledge about trachoma transmission from person to person, and stance toward preventive behavior were associated with improved practices. The odds of having improved F&E practice were 67% lower for those who reported positive normative preventive behavior than negatives. Qualitative arm: Some key informants reported village dwellers' shortage of basic knowledge; attitude and behavioral change for improved hygienic practices are the challenges. Inhabitants, including elder children, are aware of the hygiene issue though they do not practice it or have no intention to practice it. Conclusions Improved F&E practices were much lower in the study region than the regional plan to achieve.